ANALISIS TREND PERKEMBANGAN PUBLIKASI INTERNASIONAL PENELITIAN BIDANG KEANEKARAGAMAN HAYATI DI INDONESIA - Tupan Tupan (Perpustakaan Nasional RI, 2016)
This paper is an analytical study on trends of the development of international publications in Indonesian biodiversity research. The study is aimed at evaluating results of Indonesian biodiversity research included in papers that are published in Scopus indexed journals. The objectives of this study are as follows: (1) Finding out the number of international publications in biodiversity that are indexed in Scopus database during the period of 1995 to 2015 (2) Finding out international journals that publish papers on Indonesian biodiversity research (3) Finding out the productivity of researchers of Indonesian biodiversity (4) Finding out the productivity of institutions/affiliates that publish research papers on Indonesian biodiversity (5) Finding out trends of Indonesian biodiversity research development subject. Data used in this study is international publications in Indonesian biodiversity retrieved from Scopus (www.scopus.com). Data was collected in December 2015 by searching through Scopus database using keywords ‘biodiverse and Indonesia’ under the categories of article title, abstract, keyword within the period of 1995 to 2015. With this method, data on the number of annual international publications, journals that contains Indonesian biodiversity research papers, researchers, researchers’ affiliations and subjects were collected and analyzed by utilizing Microsoft Excel 2010. The analysis shows that publications of international papers on biodiversity development are found at the highest occurrence in 2015. Journal with the most papers on biodiversity research is the Biodiversity and Conservation. Most productive researcher in writing papers on biodiversity is Tscharntke, T. Institution/affiliate that publishes the most biodiversity papers is Universitat Gottingen. Country that has the most publications in Indonesian biodiversity is Indonesia. The most popular subject during the period of 1995 to 2015 is Agricultural and Biological Sciences.